2007
DOI: 10.1128/aem.01115-07
|View full text |Cite
|
Sign up to set email alerts
|

Signature-Tagged Mutagenesis of Edwardsiella ictaluri Identifies Virulence-Related Genes, Including a Salmonella Pathogenicity Island 2 Class of Type III Secretion Systems

Abstract: Edwardsiella ictaluri is the leading cause of mortality in channel catfish culture, but little is known about its pathogenesis. The use of signature-tagged mutagenesis in a waterborne infection model resulted in the identification of 50 mutants that were unable to infect/survive in catfish. Nineteen had minitransposon insertions in miscellaneous genes in the chromosome, 10 were in genes that matched to hypothetical proteins, and 13 were in genes that had no significant matches in the NCBI databases. Eight inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 78 publications
(90 reference statements)
3
73
0
Order By: Relevance
“…Although state of the art at the time, it also allowed the incidental introduction of a functional Mu prophage into these strains and their respective pir derivatives, which have since been widely used for conjugation transfer of exogenous DNA, including suicide transposon-carrying vectors, to a large number of bacterial species (E. coli [4,23,29], Klebsiella pneumoniae [7], Edwardsiella ictaluri [46], Rhizobium meliloti [33], Vibrio cholerae [28], and Erwinia carotovora [32]). In some cases, it was reported that transconjugant transposon mutants obtained using S17-1 and SM10 donor strains did not display the expected genetic linkage between the screened phenotype and insertion events or phenotype instability in transconjugants, but the reasons for these inconsistencies were not investigated (26,38).…”
Section: Discussionmentioning
confidence: 99%
“…Although state of the art at the time, it also allowed the incidental introduction of a functional Mu prophage into these strains and their respective pir derivatives, which have since been widely used for conjugation transfer of exogenous DNA, including suicide transposon-carrying vectors, to a large number of bacterial species (E. coli [4,23,29], Klebsiella pneumoniae [7], Edwardsiella ictaluri [46], Rhizobium meliloti [33], Vibrio cholerae [28], and Erwinia carotovora [32]). In some cases, it was reported that transconjugant transposon mutants obtained using S17-1 and SM10 donor strains did not display the expected genetic linkage between the screened phenotype and insertion events or phenotype instability in transconjugants, but the reasons for these inconsistencies were not investigated (26,38).…”
Section: Discussionmentioning
confidence: 99%
“…ABC60092). orf29/30 from E. ictaluri was also reported to be a single open reading frame based on a 6-fold sequencing coverage genome project of strain 93-146 (30).…”
Section: Identification Of Esejmentioning
confidence: 99%
“…E. ictaluri crosses the intestinal mucosa of channel catfish in 15 min after oral inoculation with 10 9 CFU (6). Although there are substantial descriptive data relative to the invasion, spread, and persistence of E. ictaluri in channel catfish (6)(7)(8), little is known about the molecular mechanisms of E. ictaluri fish intestinal pathogenicity and the pathogen-associated molecular patterns (PAMPs) recognized by fish.…”
mentioning
confidence: 99%